Pendidikan Karakter dalam Perspektif Islam - Musrifah (Edukasia Islamika : Jurnal Pendidikan Islam, 2016)
Recently, successful education is measured from the quantity of the students. It does not focus on the quality of education. There is even an Islamic school which does not apply the Islamic values in its management and curriculum at all. It shows that there is lack of awareness of the importance of character education. Then, what is the importance of character education? Character education is considered to be the effective way in overcoming teenage mischief and social deviation. If character educations containing Islamic values are included in the teaching and learning process, the students will be the next generation of leaders with strong character.